Results of state variety trial of new varieties of winter garlic - V.V. Skorina; F.B. Musaev; V.P. Nikulshin (Овощи России)
As a result of state variety trial in Belorussia the new varieties of winter garlic «elovezhskyi», «Soyuz», and «Yunior» were estimated, selected and included in the State register of new crops and varieties.